Rice Yields at Different Dosages of Kieserite and Planting Systems - Rozen, Nalwida; Kasim, Musliar; Dwipa, Indra (Journal of Tropical Crop Science, 2023)
Rice stands as an important staple crop in Indonesia and Asia, prompting endeavors to enhance its production. One such technology, aimed at intensifying rice cultivation, involves optimizing plant density utilizing the "jajar legowo" system. This research was conducted within community rice fields located in Pasar Ambacang, Kuranji District, Padang City, West Sumatra, Indonesia, spanning from February 2020 to June 2020. The primary objective of this study was to assess the potential of the jajar legowo planting system, in conjunction with varying dosages of kieserite, to increase lowland rice yields. The study employed a two-factor experiment in a completely randomized design. The first factor is the jajar legowo types: A (25 cm x 12.5 cm x 50 cm) and B (25 cm x 25 cm x 50 cm). The second factor involved different kieserite dosages, comprising three levels (0, 150, 300 kg.ha-1). Each treatment combination was replicated four times. Our investigation unveiled that rice panicle length reached 27.20 cm under the influence of jajar legowo type A with a kieserite dosage of 150 kg.ha-1. Conversely, with the application of jajar legowo type B alongside a kieserite dose of 300 kg.ha-1, the rice panicle length increased to 27.88 cm. The highest yield was obtained with jajar legowo type A at a dose of 300 kg.ha-1, producing 5.35 tons.ha-1. It is recommended to implement the jajar legowo type A cropping pattern with the addition of 150 kg.ha-1 of kieserite, or jajar legowo type B with the addition of 300 kg.ha-1 of kieserite.